Mechanism of apoptotic cells clearance by macrophage in MCF7 cells treated with methanol extract of centella asiatica (MECA) - Aliyu, Abdul Wahab (2019)
Apoptosis is a dynamic developmental process and is an integral part of homeostasis in higher multicellular animals. It takes place in normal tissue and is induced in abnormal cells such as breast cancer using cytotoxic chemotherapeutic agents. Defective clearance of apoptotic cancer cells in patients lead to post-chemotherapy related complication such as autoimmunity. Previous preliminary data have shown the therapeutic value of methanol extract of Centella asiatica (MECA) in modulating the clearance of apoptotic breast cancer cells by macrophage but the mechanism involved was not characterized. Thus in this current work, the mechanism of apoptosis induction and clearance of apoptotic breast cancer cells by macrophage were investigated using in vitro test system. In this study, human breast cancer cell lines (MCF7) alone or in co-culture with murine macrophage cell line J774.1A at multiplicity of infection (MOI) ratio of 1 : 2 were treated with IC50 value of MECA (13.2μg/ml) and evaluated for apoptosis induction and efferocytosis of apoptotic cells using SDS-PAGE and western blot analysis. The result demonstrated that, MECA induced apoptosis in MCF7 through significantly increase proapoptotic Bax expression. Unexpectedly, the Bcl-2 expression also increased as compared to negative control. Interestingly, MECA enhances clearance of apoptotic MCF7 by J774.1A via significant activation of ERK1/2 proteins in MECA treated transfected macrophage compared to untreated group. This is a good sign of minimal post-chemoptheraphy complications. In conclusion, plant materials with both anticancer and immunomodulatory potentials